Catalog Design As Information Medium On Ismail Multi Mandiri Convection - Dian Vannysyah; Mubarak, Husni (SEAN Institute, 2024)
Ismail multi mandiri convection is a small scale industrial clothing production company, which is a place of manufacture of apparel, such as T-shirts, polo shirts, shirts, jackets, and pants. As an effort to provide information to potential consumers about the products owned. Therefore, the need for an effective and efficient information media in order to promote each product owned by convection Ismail Multi Mandiri. As a solution, a catalog is designed as an information medium that can explain the advantages of each product in convection. The design of the catalog design at convection Ismail multi Mandiri using qualitative methods through the data collection stage with the method of observation, interviews, documentation and literature studies. The results of the study contain about the company's history, vision, mission, and the process of making catalogs using Adobe Photoshop CC 2019 application and the explanation written below. The design of this catalog is expected to be an effective and efficient means of communication for convection Ismail M ulti Mandiri with consumers.